Identifikasi Prinsip Arsitektur Bioklimatik pada Bangunan The Guha Jakarta - Alisha Zulaikha; Rina Widayanti (Jurnal Arsitektur Wastu Padma, 2025)
The increase in global temperature highlights the need for building design that responds to local climatic conditions. One relevant approach is bioclimatic architecture, a design strategy that considers the relationship between buildings, climate, user comfort, and energy efficiency. This study aims to identify the application of bioclimatic architectural principles in The Guha building in Jakarta. The research uses a qualitative descriptive method through field observation, visual documentation, and literature study. The analysis focuses on building orientation, opening placement, sun-shading strategies, material selection, landscape elements, and users’ comfort perception. The findings show that The Guha has not fully applied bioclimatic principles, particularly in terms of orientation and limited open space. However, the building demonstrates several adaptive strategies, including vegetation as shading, perforated metal as a secondary skin, openings and skylights for natural lighting, and material selection that supports spatial comfort. The Guha can be understood as a partial example of bioclimatic architectural application in an urban tropical building.